Left Atrial Deformation Predicts Pulmonary Capillary Wedge Pressure in Pediatric Heart Transplant Recipients. Issue 3 (5th July 2014) - Yeh, Jay; Aiyagari, Ranjit; Gajarski, Robert J.; Zamberlan, Mary C.; Lu, Jimmy C.
<x xml:space="preserve">Abstract</x> Background Pulmonary capillary wedge pressure (PCWP) is an important indicator in pediatric heart transplant patients, but commonly used noninvasive surrogates, such as ratio of early diastolic mitral inflow velocity to annular velocity (E/E'), have limitations in this population. This study aimed to evaluate the relation of left atrial (LA) peak systolic strain and distensibility with PCWP in pediatric heart transplant recipients. Methods Consecutive pediatric heart transplant patients were enrolled at time of cardiac catheterization, with echocardiogram immediately afterward. E/E' ratio at the lateral and medial mitral annulus, peak LA systolic longitudinal strain by speckle tracking, and LA distensibility were measured from echocardiograms and compared to invasively measured PCWP. Results In 38 patients (11.1 ± 5.8 years old), PCWP correlated with peak LA systolic strain (r = ‐0.44, P = 0.01) and LA distensibility (r= −0.43, P = 0.02), but not with E/E'. On receiver operating characteristics analysis, LA strain had a higher area under the curve than LA distensibility (0.846 vs. 0.606). LA strain <18.9% had sensitivity 62% and specificity 95%, with likelihood ratio 12.3 for PCWP ≥12. However, LA strain had lower intra‐observer and inter‐observer reproducibility than distensibility (intra‐class correlation coefficients 0.89 and 0.75 vs. 0.93 and 0.90). Conclusions Peak LA systolic strain and LA distensibility may be more useful surrogates of left ventricular filling pressure than E/E' in the pediatric heart transplant population, with greater reproducibility of LA distensibility. Longitudinal studies are needed to evaluate which parameters track changes in PCWP and clinical outcome.